CHANGED RULES OF LIMITED PARTNERSHIPS IN THE HUNGARIAN CIVIL CODE- WITH PARTICULAR REFERENCE TO THE MANAGEMENT AMENDMENTS - Lénárdné Maletics, Borbála Lénárdné Maletics (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Abstract The Act XCV of 2021 amending Act V of 2013 on the Civil Code (hereinafter: Civil Code) introduced significant changes concerning business associations in Hungary.In my study, I will examine certain amendments affecting limited partnerships, with a particular reference on the rules for the election of a limited partner as managing director and whether the corporate form is shifting from limited partnership to capital partnership under the changed provisions.
Keywords: Keywords: limited partnership, general partner, limited partner, executive director, Act V of 2013 on the Civil Code, dissolution without succession, election of a limited partner as managing director, Act XCV of 2021 amending Act V of 2013 on the Civil Code, additional monetary contributions, partnerships, capital mergers